PEMANFAATAN AIR SUNGAI BAWAH TANAH GUA SURUH UNTUK MASYARAKAT DESA PUCUNG, EROMOKO, WONOGIRI - Sigit, Agus Anggoro; Priyono, Kuswaji Dwi; Priyana, Yuli (Universitas Muhammadiyah Surakarta, 2015)
The village has a population Eromoko Pucung in District 444 families (2,354 people) which includes 7 hamlet, in the dry season is always a shortage of clean water for daily use. At the peak of the dry season are forced to buy water being sold privately at a price of Rp200,000 / car tank (volume 4 m³) for the use of approximately 20 days. In order to overcome the problems of water needs, the Pucung Village Government took the initiative to manage groundwater resources that exist in the Suruh Cave. Removal activities river water underground community empowerment aimed at utilization of underground water in the Cave Have to solving the problem ofwater supply daily needs of society in Pucung Village, District Eromoko, Wonogiri. The success of water removal program is expected to reduce the price of 1 m³ water needs of the original with a maximum price of Rp 50,000 to Rp 5,000 only.